Microevolutionary change in mimicry? Potential erosion of rattling behaviour among nonvenomous snakes on islands lacking rattlesnakes. Issue 2 (4th March 2021) - Allf, Bradley C.; Sparkman, Amanda M.; Pfennig, David W.
Abstract : Batesian mimics – harmless species that converge on the warning signals of a dangerous species – are spectacular examples of adaptation, but few documented cases involve acoustic signals. Even fewer studies have documented microevolutionary change in mimicry of any kind. Here, we describe a potential evolutionary change in acoustic mimicry. Many nonvenomous snakes vibrate their tail tip when threatened, making a sound resembling venomous rattlesnakes, which can vibrate their tail rapidly and for a long duration. When we compared this behavior between Gophersnakes from mainland California (where rattlesnakes are present) versus nearby derived island populations (where rattlesnakes are absent), we found that mainland snakes vibrated their tail for a longer duration, thereby producing a signal more similar to rattlesnakes. At the same time, we did not find evidence that island snakes differ from mainland snakes in the rate at which they vibrate their tails, or their propensity to vibrate their tails. Taken together, these data lend some support to the longstanding hypothesis that defensive tail vibration by nonvenomous snakes represents acoustic mimicry of rattlesnakes. These data further suggest that this mimetic signal may be undergoing erosion in populations where rattlesnakes are absent.